Characteristics of the cytoplasmic halo during fertilisation correlate with the live birth rate after fresh cleaved embryo transfer on day 2 in minimal ovarian stimulation cycles: a retrospective observational study - Kenji Ezoe; Tetsuya Miki; Tadashi Okimura; Kazuo Uchiyama; Akiko Yabuuchi; Tamotsu Kobayashi; Keiichi Kato (BMC, 2021)
Abstract Background Information regarding the influence of cytoplasmic events during fertilisation on the clinical outcome remains limited. The cytoplasmic halo is one of these events. A previous study that used time-lapse technology found an association of the presence and morphokinetics of the cytoplasmic halo with cleavage patterns, development to the blastocyst stage, and the ongoing pregnancy rate after blastocyst transfer. Therefore, the cytoplasmic halo may be a useful predictor of the pregnancy outcome after cleaved embryo transfer. This study evaluated the ability of the cytoplasmic halo to predict a live birth after fresh cleaved embryo transfer on day 2, and sought to identify factors potentially influencing the presence and morphokinetics of the halo. Methods A total of 902 embryos cultured in the EmbryoScope+® time-lapse system and subjected to single fresh cleaved embryo transfer were retrospectively analysed. The presence and duration of a cytoplasmic halo were annotated. The initial positions of the pronuclei were also observed. The correlation between the cytoplasmic halo and live birth was evaluated and the association of the cytoplasmic halo with patient, cycle, and embryonic characteristics was determined. Results Absence of a cytoplasmic halo was associated with a significant decrease in the likelihood of a live birth after fresh cleaved embryo transfer. Prolongation of the halo, especially the duration of central repositioning of cytoplasmic granules, had an adverse impact on the live birth rate. The characteristics of the cytoplasmic halo were not affected by the ovarian stimulation method used, female age, the serum steroid hormone level on the day of trigger, or semen quality. However, the cytoplasmic halo was significantly affected by male age, oocyte diameter, and the initial position of the male pronucleus. Conclusions Absence or prolongation of the cytoplasmic halo was negatively correlated with the live birth rate after fresh cleaved embryo transfer. The characteristics of the cytoplasmic halo were strongly associated with oocyte diameter, male age, and the initial position of the male pronucleus. These findings indicate that the characteristics of the cytoplasmic halo can be used to select more competent embryos for transfer at the cleavage stage.